New alternating D–A1–D–A2 copolymer containing two electron‐deficient moieties based on benzothiadiazole and 9‐(2‐Octyldodecyl)‐8H‐pyrrolo[3, 4‐b]bisthieno[2, 3‐f:3', 2'‐h]quinoxaline‐8, 10(9H)‐dione for efficient polymer solar cells. Issue 1 (11th August 2015) - Keshtov, M. L.; Kuklin, S. A.; Godovsky, D. Y.; Khokhlov, A. R.; Kurchania, R.; Chen, F. C.; Koukaras, Emmanuel N.; Sharma, G. D.
ABSTRACT: A novel D–A1 –D–A2 copolymer denoted asP1 containing two electron withdrawing units based on benzothiadiazole (BT) and 9‐(2‐octyldodecyl)−8H‐pyrrolo[3, 4‐b] bisthieno[2, 3‐f:3′, 2′‐h]quinoxaline‐8, 10(9H)–dione (PTQD) units was synthesized and characterized. The resulting copolymer exhibits a broad‐absorption spectrum, relatively deep lying HOMO energy level (−5.44 eV) and narrow optical bandgap (1.50 eV). Bulk heterojunction (BHJ) polymer solar cells (PSCs) based onP1 as donor and PC71 BM as acceptor with optimized donor to acceptor weight ratio of 1:2 and processed with DIO/CB solvent showed good photovoltaic performance with power conversion efficiency of 6.21% which is higher than that of the device processed without solvent additive (4.40%). The absorption and morphology investigations of the active layers indicated that structural and morphological changes were induced by the solvent additive. This higher power conversion efficiency could be mainly attributed to the absorption enhancement and improved charge transported in the active layer induced by the better nanoscale morphology of the active layer. This study demonstrated that a copolymer with two different acceptor moieties in the backbone may be promising candidate as donor copolymer for solution processed BHJ PSCs. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 155–168 Abstract : A novel D–A1–D–A2 copolymer containing two electron withdrawing units based on benzothiadiazole (BT) and 9‐(2‐octyldodecyl)−8H‐pyrrolo[3, 4‐b] bisthieno[2, 3‐f:3′, 2′‐h]quinoxaline‐8, 10(9H)‐dione (PTQD) units was synthesized and used as donor for the fabrication of bulk heterojunction polymer solar cells. The polymer solar cell with optimized P1:PC71BM active layer processed with DIO/CB showed power conversion efficiency of 6.21%.